Co‐development of a risk assessment strategy for managed relocation. Issue 3 (9th August 2021) - Karasov‐Olson, Aviv; Schwartz, Mark W.; Skikne, Sarah A.; Hellmann, Jessica J.; Olden, Julian D.; Lawrence, David J.; Morisette, Jeffrey T.; Schuurman, Gregor W.; Allen, Sarah; Brigham, Christy A.; Buttke, Danielle; Miller‐Rushing, Abraham J.; et al.
Abstract: Resource managers face mounting challenges when it comes to the implementation of climate change adaptation strategies. Novel adaptation strategies, such as managed relocation, frequently entail embracing substantial risk of unintended harm to the focal ecosystems, in an effort to alleviate serious threats to biological diversity (e.g. extinction). Assessing ecological risks associated with different adaptation strategies is consistently called for, but the process for doing so is often undefined. Here, we describe a collaboration amongst university researchers, agency scientists and resource managers to create a set of ecological risk assessment protocols for managed relocation decision support. These protocols are designed to foster a rigorous assessment of ecological risk, while simultaneously being flexible and easy to use. We describe a collaborative process through which we developed a structure for assessing risk that includes a suite of 17 risk categories aggregated into six overarching groups, which is placed within a broader decision context for managed relocation (e.g. evaluating feasibility, social acceptability). Our risk scoring includes both scaled estimates of risk and perceived confidence in those estimates. Because of differences in the importance of risk categories, we do not recommend a quantitative summary across risk areas, but suggest decision makers make decisions based on three criteria: overall confidence that a proposed action can be confidently evaluated; low overall level or risk across categories; and no single risk category that is highly likely to result in severe adverse outcomes. Abstract : Implementation of novel climate change adaptation strategies requires a thorough assessment of the risks involved in those actions. We describe standardised risk assessment protocols for managed relocation, the intentional movement of a species beyond their historical geographical range. These protocols were developed in partnership among U.S. National Park Service Climate Program Staff, Parks managers and university scientists.